Atmospheric aging increases the cytotoxicity of bare soot particles in BEAS-2B lung cells. Issue 5 (4th May 2023) - Pardo, Michal; Czech, Hendryk; Offer, Svenja; Sklorz, Martin; Di Bucchianico, Sebastiano; Hartner, Elena; Pantzke, Jana; Kuhn, Evelyn; Paul, Andreas; Ziehm, Till; Zhang, Zhi-Hui; Jakobi, Gert; et al.
Abstract: Soot particles (SP) are ubiquitous components of atmospheric particulate matter and have been shown to cause various adverse health effects. In the atmosphere, freshly emitted SP can be coated by condensed low-volatility secondary organic and inorganic species. In addition, gas-phase oxidants may react with the surface of SP. Due to the chemical and physical resemblance of SP carbon backbone with polyaromatic hydrocarbon species and their potent oxidation products, we investigated the biological responses of BEAS-2B lung epithelial cells following exposure to fresh- and photochemically aged-SP at the air–liquid interface. A comprehensive physical and chemical aerosol characterization was performed to depict the atmospheric transformations of SP, showing that photochemical aging increased the organic carbon fraction and the oxidation state of the SP. RNA-sequencing and qPCR analysis showed varying gene expression profiles for fresh- and aged-SP. Exposure to aged-SP increased DNA damage, oxidative damage, and upregulation of NRF2-mediated oxidative stress response genes compared to fresh-SP. Furthermore, aged-SP augmented inflammatory cytokine secretion and activated AhR-response, as evidenced by increased expression of AhR-responsive genes. These results indicate that oxidative stress, inflammation, and DNA damage play a key role in the cytotoxicity of SP in BEAS-2B cells, where aging leads to higher toxic responses. Collectively, our results suggest that photochemical aging may increase SP toxicity through surface modifications that lead to an increased toxic response by activating different molecular pathways. GRAPHICAL ABSTRACT: UF0001